PRIMEIRO RELATO DE Cercospora spp. EM ERVA-CIDREIRA NO MATO GROSSO DO SUL - Gomes Cavalcanti , Vittor; Fernandes da Costa , Brenda; André Sganzerla Graichen , Felipe; Henrique Martinez Blanco , Neder; de Souza da Silva, Talísia; Ferreira Machado , Euler (ANAIS DO ENIC, 2026)
--